Strengthening Education Quality in East Asia - Patrinos, Harry Anthony (World Bank, Washington, DC, 2014)
This study argues that in order to improve education quality, it is crucial to monitor each policy domain that makes up the whole. To help government's identify best practice policies, the World Bank created a framework to benchmark education system policies across the world. The framework is called system assessment and Benchmarking for Education Results (SABER). This study presents the first, pilot application of SABER in 14 economies in East Asia-a region where improving the quality of education remains the key challenge. It outlines the SABER framework for eight education policy domains; affording cross-country comparisons, in combination with evidence on which program work. Under each domain, the latest empirical evidence on how these policies and practices relate to education quality is presented, along with the indicators used to measure them. The report concludes that the key to a successful education system is not just success in any one domain, but an overall alignment of policies in many aspects of the education system.